(untitled) (Al-Academy, 2019)
The research dealt with the study of the element of time in the cinematic language and the role it plays in creating the aesthetic meanings in the documentary film by means of the various structural constructions with which time is constructed. The research included the introduction and the problem of research, which was represented by the following question: (Did the documentary film adopt the values of time formats in the fiction film or it created for itself special linguistic formulations and models which achieve the aesthetic concept?). It also included the importance of research, the need for it and its goal in addition to clarifying the limits of research.The theoretical framework included three sections the first of which is the concept of time. It focused on studying time objectively and its origin in philosophy, life, human experience, human action, cinema, drama, and the event. The concept of time in the cinema was then defined. The second section: the documentary film. It contains the basic pillars in the artistic construction of the documentary film and the structure methods.The third section / time in the documentary film. It is interested in studying the time structures, time movements and time transfers and how to address them.The research procedures included the applications adopted by the researcher to analyze the selected sample and reach the goal of the research. They included the methodology adopted in the research, the reasons for selecting the sample, the research tool and the analysis unit.The sample was analyzed and the final results were derived. The most prominent of these were the multiplicity of treatments in the film structure, which gave a large space for the dynamics of time within the structure of the documentary film, and the qualitative overlap of the documentary films led to the diversity of the temporal structure, which gave an aesthetic depth to the structure of the documentary film. The conclusions drawn were also presented in addition to a list of sources and references used by the researcher in Arabic and foreign languages in addition to the summary of the study in English